Collage as Queer Methodology: The Pleasures and Politics of Trans and Queer Photographic Representations - Ball, Jack (Curtin University, 2021)
This practice-led research project is a critical feminist engagement with the messy complexities of making, consuming and exhibiting imagery. I use a range of material processes to develop large-scale photographic series that explore intimacy and a continued reconfiguring of the body. I consider the ethical intricacies of photographic practice and interrogate how a feminist and queer politics of ruining and remaking can inform an approach to my own practice and participation in image culture.